Permutation Tests for Comparing Multidimensional Populations in Economics Research - Dominika POLKO-ZAJAC (Communications of International Proceedings, 2021)
When comparing multidimensional populations, a hypothesis about the equality of mean vectors in two populations is most often verified. A classical test to verify this hypothesis is the Hotelling T2 test. Comparing may also apply to test the hypothesis of equality of variance-covariance matrices in these populations. In addition to classical tests, it is also possible to refer to simulation randomization methods to test the significance of differences between the studied populations. The paper presents a permutation procedure for identifying differences between two multidimensional populations. A simulation study was conducted to determine the size and power of these tests. The advantage of the presented method is that it can be used when samples are taken from any type of continuous distributions in the population. Tests can be used in the analysis of multidimensional economics phenomena.
Keywords: Permutation Tests; Comparing Populations; Power Of A Test; Location-Scale Tests.